2004
DOI: 10.1029/2004gl020605
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and numerical studies of density modulated whistlers

Abstract: [1] Recently, observations from laboratory experiments, which are relevant to space observations as well, have conclusively revealed the amplitude modulation of whistlers by low-frequency perturbations. Our objective here is to present theoretical and simulation studies of amplitude modulated whistler packets on account of their interaction with background low-frequency density perturbations that are reinforced by the whistler ponderomotive force. Specifically, we show that nonlinear interactions between whist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…whistler) waves (Kostrov, 2003). Recent numerical simulations of electron cyclotron waves (Eliasson and Shukla, 2004) (as well as earlier ones, by Hasegawa, 1970Hasegawa, , 1972) also predict such a behaviour.…”
Section: Introductionsupporting
confidence: 53%
“…whistler) waves (Kostrov, 2003). Recent numerical simulations of electron cyclotron waves (Eliasson and Shukla, 2004) (as well as earlier ones, by Hasegawa, 1970Hasegawa, , 1972) also predict such a behaviour.…”
Section: Introductionsupporting
confidence: 53%
“…In Refs. 20 and 21 it was later shown that these ponderomotive forces are reinforced due to the interaction of the whistler packets with the background low density perturbations 20 . In addition to the low density perturbations observed in our simulations (see Fig.10), the formation of wave packets of the perturbed magnetic field are also evident (see Fig.11, left frame).…”
Section: Low Frequency Modulationsmentioning
confidence: 96%
“…The amplitude and spatial distribution of chorus waves can be strongly influenced by ambient plasma density fluctuations through ducting [e.g., Koons 1989, and references therein] or modulated growth rates [Li et al, 2011]. Also, correlations between chorus wave amplitude and density structure may be expected if the waves modify the plasma density through ponderomotive interactions [e.g., Eliasson and Shukla, 2004] or if nonlinear sheath rectification effects are present [Boehm et al, 1994]. In situ observations have correlated large-scale (hundreds of kilometers) density fluctuations with enhanced chorus wave power [Scarf and Chappell, 1973;Koons, 1989].…”
Section: Introductionmentioning
confidence: 99%